2021
DOI: 10.1186/s12913-021-06889-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in Guatemala’s Public Primary Care System: A Needs Assessment Using the Health System Building Blocks Framework

Abstract: Background Uncontrolled hypertension represents a substantial and growing burden in Guatemala and other low and middle-income countries. As a part of the formative phase of an implementation research study, we conducted a needs assessment to define short- and long-term needs and opportunities for hypertension services within the public health system. Methods We conducted a multi-method, multi-level assessment of needs related to hypertension within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…This project sought to improve hypertension control in Guatemala in intervention districts in rural and indigenous communities in 5 provinces ( 12 , 13 ). A needs assessment conducted at the outset showed that the health care system, part of the external environment , is like many in low- and middle-income countries: the public sub-system requires additional funding and system strengthening to ensure sufficient human resources and medications to adequately meet need across the country ( 14 ). Within Guatemala's Ministry of Health, actors at multiple levels take part in delivery of the intervention (national-level actors based in the capital, provincial-level Health Areas, and district-level providers), and patients, families, and community members are beneficiaries with important insight about implementation and access.…”
Section: Context: Understanding Deep-rooted Inequitiesmentioning
confidence: 99%
“…This project sought to improve hypertension control in Guatemala in intervention districts in rural and indigenous communities in 5 provinces ( 12 , 13 ). A needs assessment conducted at the outset showed that the health care system, part of the external environment , is like many in low- and middle-income countries: the public sub-system requires additional funding and system strengthening to ensure sufficient human resources and medications to adequately meet need across the country ( 14 ). Within Guatemala's Ministry of Health, actors at multiple levels take part in delivery of the intervention (national-level actors based in the capital, provincial-level Health Areas, and district-level providers), and patients, families, and community members are beneficiaries with important insight about implementation and access.…”
Section: Context: Understanding Deep-rooted Inequitiesmentioning
confidence: 99%
“…This should translate to a broad needs and contextual assessment, considering the local (ICT) context, workflow, and sociopolitical barriers to accessing high-quality care. Health system assessment tools and frameworks can help structure the review of the current obstacles and facilitators surrounding CVD prevention and care [ 100 101 ], which often require a mixed-methods approach. User-centred and co-design principles are necessary to contextualise interventions and make them more effective [ 102 103 ].…”
Section: Roadblocks and Solutions To Implement Digital Health Interve...mentioning
confidence: 99%
“…This effort is being led by the Institute of Nutrition of Central America and Panama (INCAP) in partnership with Guatemala's Ministry of Health and Social Welfare (MoH) (8). The multilevel multicomponent hypertension intervention program (thereafter referred to as "program") consists of a core evidence-based intervention (EBI), protocol-based stepped-care hypertension treatment, and ve implementation strategies, which have been previously described (7,9,10). In March 2020, 9 months after launching the program, COVID-19 cases were growing in Guatemala and a national-level response with lockdowns and signi cant disruptions to rural communities and healthcare services occurred.…”
Section: Introductionmentioning
confidence: 99%